A Decade of Research on Origen’s Homilies on the Psalms (Codex Monacensis Graecus 314) - José Alviar (Warszawskie Studia Teologiczne)
Slightly more than a decade has passed since the momentous discovery in Munich of 29 Greek homilies by Origen on the Psalms. In all this time, the new material has been the object of intense study on the part of scholars. The present article offers a description and classification of the research published to date, identifying the principal avenues of investigation opened by access to Origenistic texts hitherto unknown to modern scholars.